Analisis Pendapatan Asli Daerah Provinsi Banten - Wibowo, Tasya Fatmawati; Soebagiyo, Daryono (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2025)
Regional revenue refers to all income received by a region, sourced from various components that contribute to the increase in the region's net wealth. High Regional Original Income (PAD) can be an indicator that the implementation of regional autonomy is effective, where local governments have the ability to finance various development activities independently without relying solely on funds from the central government. This study aims to analyze the impact of several factors on PAD in the regencies and cities of Banten Province from 2016 to 2020, using panel data regression analysis. The factors analyzed include Gross Regional Domestic Product (PDRB), population, government expenditure, and Regional Minimum Wage (UMR). The results of the validity test with the Fixed Effects model approach show that population size has a positive impact on PAD, meaning that the larger the population, the greater the potential revenue from taxes and levies. Conversely, government expenditure has a negative effect on PAD, indicating that an increase in government expenditure in the short term may reduce the PAD available to the region. Meanwhile, the PDRB and UMR variables did not show a significant impact on PAD during the analyzed period, highlighting the complexity of the relationship between economic factors and regional income, which requires further attention in regional development policies.